2022
DOI: 10.1371/journal.pone.0274335
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the CYP1B1 gene reveals thirteen novel disease-causing variants in consanguineous Pakistani families causing primary congenital glaucoma

Abstract: Background Primary congenital glaucoma (PCG) is a heterogeneous rare recessively inherited disorder prevalent in regions with high consanguinity. Disease phenotype is associated with increased intra ocular pressure and is a major cause of childhood blindness. Sequence variations in Cytochrome P450 1B1 (CYP1B1) gene are a major cause of PCG. Current study was conducted to screen CYP1B1 gene in highly consanguineous PCG affected families from Pakistani population consistent with the autosomal recessive pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Visual outcomes have been correlated with factors such as age at diagnosis, corneal clouding, and the presence of concurrent amblyopia ( 61 , 62 ). Recent research has also identified associations with genetic mutations ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual outcomes have been correlated with factors such as age at diagnosis, corneal clouding, and the presence of concurrent amblyopia ( 61 , 62 ). Recent research has also identified associations with genetic mutations ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCG is characterized by the abnormal anatomical structure of the TM and anterior chamber angle, thus resulting in aqueous outflow resistance and IOP elevation in infancy ( 45 ). With the progression of the disease, the affected eye may display a larger cornea or eyeball size than normal individuals, which is named “hydrophthalmos” or “buphthalmos.” Of note, these two terms involve different etiologies and clinical features.…”
Section: Disorder Of Biomechanical Homeostasis In Ocular Diseasesmentioning
confidence: 99%
“…Glaucoma can be categorized into three groups, i.e., primary angle-closure glaucoma (PACG), primary open-angle glaucoma (POAG), and normal tension glaucoma (NTG). PACG is the rapidly progressive glaucoma, and it occurs when the iris is very close to the drainage angle in the eye . The iris can end up blocking the drainage angle.…”
Section: Manageable Diseases Through Eyesmentioning
confidence: 99%
“…PACG is the rapidly progressive glaucoma, and it occurs when the iris is very close to the drainage angle in the eye. 115 The iris can end up blocking the drainage angle. When the drainage angle gets No one knows the exact reason why the optic nerve becomes damaged when the eye pressure is normal.…”
Section: Glaucomamentioning
confidence: 99%